INTERACT: Interactive E-Learning for Children with Autism - Samonte, Mary Jane C.; Cape, Jason Jean K.; Kalaw, Marielle Nicole O.; Valentino, Bernice Samantha F. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Mainstreaming is a combination of regular and special education classes. Regular classes are for those students with usual time-phasing schedules, while special classes are focused on special education (SPED) that involves students with difficulty in their motor skills and academics. One of the problems faced by SPED is the students struggle with lesson retention. This is due to a limitation in methods to practice, review and recall their lessons after classroom period. Thus, the researchers created an interactive e-Learning website for children with Autism, that will serve as a supplementary tool for special classes. Lessons provided in the website are designed by skilled teachers who are experts in special education. Since SPED teachers have access to the website, they can check the students’ performance from the evaluation records. Also, guardians of special children can actively participate in the students’ journey towards learning.